2001
DOI: 10.1097/00000658-200112000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy Versus Mini-Laparotomy Cholecystectomy

Abstract: Operating time was longer and convalescence was smoother for LC compared with MC. Further analyses of LC versus MC are necessary regarding surgical training, surgical outcome, and health economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 23 publications
5
86
1
8
Order By: Relevance
“…In both trials, conversion to open cholecystectomy was necessary for more than 20% of the patients [9,10]. In contrast, among patients with uncomplicated gallstone disease (i.e., without CBD stones or need for ES), the conversion rate for LC is known to be 3% to 5% [2,18,20,21,[23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In both trials, conversion to open cholecystectomy was necessary for more than 20% of the patients [9,10]. In contrast, among patients with uncomplicated gallstone disease (i.e., without CBD stones or need for ES), the conversion rate for LC is known to be 3% to 5% [2,18,20,21,[23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, we feel that this has little bearing on the 'mini' approach, which results in far less morbidity than the conventional operation. In all probability, a more valid comparison is available in several reports comparing mini approaches for cholecystectomy and laparoscopic cholecystectomy [16]. In a large randomized single-blinded control Swedish study of >700 patients, there was no difference between the mini and laparoscopic cholecystectomy, apart from the laparoscopic approach being more expensive [17].…”
Section: Discussionmentioning
confidence: 99%
“…MAU was used in 112 patients (mean age 38 years, range 26-57) between 1991 and 2001; the mean (range) stone size was 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)) mm, with 30 stones in the upper, 69 in the mid-and 13 in the lower ureter. In 15 patients the stones were impacted and there were signs of infection in the proximal ureter.…”
Section: Methodsmentioning
confidence: 99%
“…Four SRs (ANDEM, 1994;Downs, 1996;Korolija, 2004;Keus, 2006a;Keus, 2006b), two RCTs (Mimica, 2000;Ros, 2001), three cohort studies (Devereaux, 2005;Elder, 1996;Finan, 2006), one CPG (Zacks, 2002), one cross-sectional study (Collet, 1997) and one case series (Ibrahim, 2006) were included. One SR concluded that laparoscopic techniques take longer than conventional techniques.…”
Section: Effectiveness Of Laparoscopic Cholecystectomymentioning
confidence: 99%